UJI TOKSISITAS FRAKSI n-BUTANOL BERUWAS LAUT (Scaevola taccada (Gaertn.) Roxb.) DENGAN METODE BRINE SHRIMP LETHALITY TEST - Irma Santi; Sitti Nurbaezurah (As-Syifaa Jurnal Farmasi, 2013)
The research on Toxicity Test Of n-Butanol Fraction Beruwas Laut (Scaevola taccada (Gaertn.) Roxb.) Using Brine Shrimp Lethality Test Method an investigation with larvaes Artemia salina Leach as test animal which is intended to potential toxic test. Each treatment is done the replication of research 3 times of the fraction n-butanol beruwas laut concentration are 0,1 μg/ml, 1 μg/ml, 10 μg/   ml, 100 μg/ml and solvent control n-butanol by same concentration. The result is against larvae that died 24 hours after component test was given. Through the data, LC50 value of n-butanol fraction Beruwas Laut (Scaevola taccada (Gaertn.) Roxb.) was analyzed by probit analysis. This research indicated concentration of fraction n-butanol of beruwas laut (Scaevola taccada (Gaertn.) Roxb.) could kill larvae by the concentration of 0,1 μg/ml, 1 μg/ml, 10 μg/ml and 100 μg/ml. The result of probit analysis indicated that LC50 value of fraction Beruwas Laut of (Scaevola taccada (Gaertn.) Roxb.) was 12,16 ± 11,23 µg/mL. Research result and probit analysis indicated that n-butanol fraction of beruwas laut (Scaevola taccada (Gaertn.) Roxb.) toxic characteristic by LC50 value was 12,16 ± 11,23 µg/ml. On according Meyer test result explained toxic about Artemia salina Leach when extract had LC50  less of 1000 µg/mL.Key Words : Toksisitas Test, n-butanol Scaevola taccada (Gaertn.)Roxb), Brine Shrimp Lethality Test